2022
DOI: 10.9734/arjom/2022/v18i130355
|View full text |Cite
|
Sign up to set email alerts
|

Modified Classes of Regression-Type Estimators of Population Mean in the Presences of Auxiliary Attribute

Abstract: The use of relevant information from auxiliary variable at the estimation stage and design stage to obtain reliable and efficient estimate is a common practice is a sample survey. But situations arise when the available auxiliary information are attribute in nature. There are some existing estimators based on auxiliary attribute in literature, however, they are less efficient when the bi-serial correlation between the study variable and auxiliary attribute is negative. Also, some depend on an unknown parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In this research, we proposed an improved modified regression estimators for the estimation of population mean in the presence of auxiliary attribute. The results of the empirical study revealed that the proposed estimators are more efficient than sample mean and Audu et al 1 estimators. This implies that the proposed estimators have great chance of producing precise estimate.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…In this research, we proposed an improved modified regression estimators for the estimation of population mean in the presence of auxiliary attribute. The results of the empirical study revealed that the proposed estimators are more efficient than sample mean and Audu et al 1 estimators. This implies that the proposed estimators have great chance of producing precise estimate.…”
Section: Discussionmentioning
confidence: 93%
“…Table 4 shows MSEs and PREs of the suggested and some existing estimators using dataset 2. The result shows that the suggested estimators have minimum MSEs and higher PREs compared to the conventional estimators and Audu et al 1 estimators.…”
Section: Estimatorsmentioning
confidence: 83%
See 3 more Smart Citations